KAJIAN TEOLOGI PRAKTIS MENGENAI KEHADIRAN DALAM IBADAH PEMUDA DI JEMAAT GMIM SION PERAK SORONG - Oroh, Merry (PT. Giat Konseling Nusantara, 2025)
Church youth are often referred to as the backbone of the Church. Therefore youth also have an important role in the life of the Church. Many youths make worship only as a routine activity with certain intentions in worship. In addition, differences in family economic background also have an influence on the presence of young people in worship. This thesis contains the results of research on GMIM Sion Perak Sorong youth congregation. From the research results, the authors found that there were problems in youth organizations regarding their minimal attendance at worship. Therefore, the Church, in this case pastors and special ministers as well as parents, must play a role in motivating and guiding young people to be more active and earnest in participating in worship.